2017
DOI: 10.1508/cytologia.82.25
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Chromosome Analysis of Two Chaetodontid Fishes (Perciformes, Chaetodontidae)

Abstract: We report the first chromosome analysis in the Indian vagabond butterflyfish (Chaetodon decussatus) and lined butterflyfish (C. lineolatus) from Andaman Sea, Phuket Province, Thailand. Kidney cell samples were taken from four male and four female fishes. The mitotic chromosome preparation was directly prepared from kidney cells. The chromosomes were stained with conventional and Ag-NOR staining techniques. The results showed that the diploid chromosome number of C. decussatus and C. lineolatus was 2n=48, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“… L = large chromosome; M = medium chromosome; S = small chromosome. References: [ 60 ] Arai and Yamamoto, 1981 [ 61 ]; Galetti et al (2006) [ 57 ]; Arai and Inoue (1975) [ 62 ]; Supiwong et al (2017a) [ 64 ]; Supiwong et al (2017b) [ 63 ]; Na Nongkhai (2014) [ 65 ]; Molina et al (2013) [ 66 ]; Affonso et al (2001) [ 67 ]; Nagpure et al (2006) [ 68 ]; Boonsuk (2013) [ 69 ]; Ojima and Yamamoto (1990) [ 70 ]; Jumrusthanasan and Supiwong (2015) [ 54 ]; Supiwong et al (2015) [ 71 ]; Sonsrin and Pinthong, 2018. …”
Section: Discussionmentioning
confidence: 99%
“… L = large chromosome; M = medium chromosome; S = small chromosome. References: [ 60 ] Arai and Yamamoto, 1981 [ 61 ]; Galetti et al (2006) [ 57 ]; Arai and Inoue (1975) [ 62 ]; Supiwong et al (2017a) [ 64 ]; Supiwong et al (2017b) [ 63 ]; Na Nongkhai (2014) [ 65 ]; Molina et al (2013) [ 66 ]; Affonso et al (2001) [ 67 ]; Nagpure et al (2006) [ 68 ]; Boonsuk (2013) [ 69 ]; Ojima and Yamamoto (1990) [ 70 ]; Jumrusthanasan and Supiwong (2015) [ 54 ]; Supiwong et al (2015) [ 71 ]; Sonsrin and Pinthong, 2018. …”
Section: Discussionmentioning
confidence: 99%
“…All specimens were maintained in aerated, flowing seawater aquaria until analysis. Mitotic chromosome preparations were made from anterior kidney after in vivo treatment using a method modified from Chen and Ebeling (1968), Gold et al (1990), Kasiroek et al (2017) and Supiwong et al (2017). The chromosomes were stained with 10% Giemsa s for 30 min (Chooseangjaew et al 2017) and identified for NORs by Ag-NOR staining technique (Howell andBlack 1980, Sangpakdee et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In the present work, cytogenetical analyses by conventional staining and Ag-NOR banding techniques were carried out on two wild species from the Andaman Sea, Thailand including C. triangulum and C. andamanensis. The study would also improve our understanding of karyotype evolution mechanism and speciation in the family Chaetodontidae (Supiwong et al 2017), and increase knowledge available for implementation of polyploidy manipulation, hybridization, sex control and other genetic improvements in the future.…”
mentioning
confidence: 99%
“…In Thailand, including Indochina and the northern Malay peninsula, Alongklod Tanomtong and coworkers have recently focused on fish karyotype analysis and have published 15 reports in Cytologia over the last 2 years on the following fish species: Humpback cardinalfish, Fibramia lateralis (Kasiroek et al 2017a); Banggai cardinalfish, Pterapogon kauderni (Kasiroek et al 2017b); triangle butterflyfish, Chaetodon triangulum and yellow butterflyfish, C. andamanensis (Supiwong et al 2017a); Indian vagabond butterflyfish, Chaetodon decussatus and Lined butterflyfish, C. lineolatus (Supiwong et al 2017b); Nile tilapia, Oreochromis niloticus (Sriuttha et al 2017); three-spot damselfish, Dascyllus trimaculatus (Getlekha et al 2017); ocellated dragonet, Synchiropus ocellatus and picturesque dragonet, S. picturatus (Kasiroek et al 2017c); crystal eye catfish, Hemibagrus wyckii (Supiwong et al 2017d); Chevey s sheetfish, Micronema cheveyi (Pinthong et al 2017); F 1 hybrid catfish: Mekong giant catfish, Pangasianodon gigas striped catfish, P. hypophthalmus and spot pangasius, Pangasius larnaudii Pangasianodon hypophthalmus (Sreeputhorn et al 2017); whitecheek monocle bream, Scolopsis vosmeri (Supiwong et al 2017c); snakehead fishes, Channa marulius and C. marulioides (Sarasan et al 2018); Hihgfin barb fish, Cyclocheilichthys armatus (Chaiyasan et al 2018); black lancer, Bagrichthys majusculus (Supiwong et al 2018); and longfin carp, Labiobarbus leptocheilus (Saenjundaeng et al 2018).…”
Section: Post-war Trajectory and A New Ichthyologic Trendmentioning
confidence: 99%